Hexagonal metal complex based mechanically robust transparent ultrathin gold µECoG for electro-optical neural interfaces - Duhee Kim; Murali Bissannagari; Boil Kim; Nari Hong; Jaeu Park; Hyeongtae Lim; Junhee Lee; Jungha Lee; Yoon Kyoung Kim; Youngjae Cho; Kwang Lee; Junghyup Lee; et al. (npj Flexible Electronics)
Abstract Transparent electro-optical neural interfacing technologies offer simultaneous high-spatial-resolution microscopic imaging, and high-temporal-resolution electrical recording and stimulation. However, fabricating transparent, flexible, and mechanically robust neural electrodes with high electrochemical performance remains challenging. In this study, we fabricated transparent (72.7% at 570 nm), mechanically robust (0.05% resistance change after 50k bending cycles) ultrathin Au microelectrodes for micro-electrocorticography (µECoG) using a hexadentate metal-polymer ligand bonding with an EDTA/PSS seed layer. These transparent µECoG arrays, fabricated with biocompatible gold, exhibit excellent electrochemical properties (0.73 Ω·cm2) for neural recording and stimulation with long-term stability. We recorded brain surface waves in vivo, maintaining a low baseline noise and a high signal-to-noise ratio during acute and two-week recordings. In addition, we successfully performed optogenetic modulation without light-induced artifacts at 7.32 mW/mm2 laser power density. This approach shows great potential for scalable, implantable neural electrodes and wearable optoelectronic devices in digital healthcare systems.